2002
DOI: 10.1103/physrevb.66.184511
|View full text |Cite
|
Sign up to set email alerts
|

Effects of superconducting gap anisotropy on the flux flow resistivity inY(Ni1xPt

Abstract: The microwave complex surface impedance Zs of Y(Ni1−xPtx)2B2C was measured at 0.5 K under magnetic fields H up to 7 T. In nominally pure YNi2B2C, which is a strongly anisotropic s-wave superconductor, the flux flow resistivity ρ f calculated from Zs was twice as large as that expected from the conventional normal-state vortex core model. In Pt-doped samples where the gap anisotropy is smeared out, the enhancement of ρ f is reduced and ρ f approaches to the conventional behavior. These results indicate that ene… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…In other words, the mean free path of quasi-particles inside the vortex core, l core = v F s core % 200 Å is much shorter than that outside by one order of magnitude, and is rather comparable to the core radius, n % 40 Å, where v F % 3.5 Â 10 4 m/s is the Fermi velocity estimated from the relation hx 0 ¼ D 0 =k F n. This tendency seems to be very strange at the first sight. However, the short mean free path of the quasi-particle inside the vortex core was also observed in the flux-flow study of cuprate superconductors [11,[29][30][31] and Y 2 C 3 [32]. In the cuprate case, the mean free path inside the vortex core is also much shorter than that outside and close to the core radius, l core $ n ( l M .…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…In other words, the mean free path of quasi-particles inside the vortex core, l core = v F s core % 200 Å is much shorter than that outside by one order of magnitude, and is rather comparable to the core radius, n % 40 Å, where v F % 3.5 Â 10 4 m/s is the Fermi velocity estimated from the relation hx 0 ¼ D 0 =k F n. This tendency seems to be very strange at the first sight. However, the short mean free path of the quasi-particle inside the vortex core was also observed in the flux-flow study of cuprate superconductors [11,[29][30][31] and Y 2 C 3 [32]. In the cuprate case, the mean free path inside the vortex core is also much shorter than that outside and close to the core radius, l core $ n ( l M .…”
Section: Resultsmentioning
confidence: 71%
“…Recent reinvestigation [8] showed that the effect of overlap of vortex cores increased the zero-energy density of state rapidly, and the constant a becomes about 1.25 at low magnetic fields. However, for nodal superconductors, such as p-wave [9], d-wave [10] and anisotropic s-wave superconductors [11], q f behaves as q f ðBÞ / ffiffiffi B p . A physical origin of this additional dissipation is the Doppler shift of quasiparticles leaked out in directions of nodes [12].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, for an isotropic gap case, the Bardeen-Stephen (BS) theory [14] obviously obeys Eq.(1). On the other hand, in nodal and modulated gap case, an enhancement with α > 1 at low B region has been also observed experimentally [15][16][17][18]. This also suggests that the so-called "Volovik effect" (the effect of the Doppler shift on QPs disperse caused by the circulating supercurrents) is not important for the flux-flow in low B region, although it succeeded to explain B dependences of the specific heat and the thermal conductivity.…”
mentioning
confidence: 64%
“…In any case, the magnetic field dependence of ρ f of LiFeAs are very similar to that of MgB 2 , implying that the s ± -wave SC behaves essentially similarly to the s ++ -wave SC so far as the flux-flow is concerned. The insensitivity of the flux-flow to the sign change for single-gap SCs has been already known for single-gap SCs; although the anisotropic s-wave SC and the d-wave SC differ from each other in the sign change of the order parameter, ρ f of both SCs show the B-linear dependence with α > 1 [16][17][18]. Our present result shows that the insensitivity shown up in the flux-flow is applicable also for multiple-gap SCs.…”
mentioning
confidence: 77%
“…5) The high DOS was also suggested by the specific heat data, 6) and was consistent with the large dissipation observed by the microwave surface impedance experiment in the mixed state. 7,8) In this context, the HTSCs are very interesting materials, since it is almost established that the condensate wave function has a d-wave symmetry in these materials. 9,10) Thus, the vortex core of the HTSC can be regarded as a naturally prepared nanometer-scale space for QPs embedded in the d-wave condensate.…”
Section: Introductionmentioning
confidence: 99%